PRELIMINARY BOTANICAL ASSESSMENT OF PRODUCTION CHALLENGES OF CASHEW (ANACARDIUM OCCIDENTALE L.) IN LAFIA, NASARAWA STATE, NIGERIA - T. P. TERNA, E. H. KWON-NDUNG, H. AMAOBI, J. I. OKOGBAA, G. F. AKOMOLAFE, (International Multidisciplinary Research Journal, 2018)
The aim of this study was to investigate the production and challenges of cashew farming in Lafia, Nigeria. The study area was divided into five zones. Fifty semi-structured questionnaires were administered to the farmers. The results showed that only males are engaged in cashew farming and slightly above 95% are married and just about 44% are aged between 21-40 y. Over 95% of farmers disclose that cashew production is seasonal; slightly above 73% disclose that diseases and pests are major challenges in cashew cultivation. Over 64% are of the opinion that these diseases and pests are responsible for yield reduction. Slightly above 52% disclose that yellow cashew is the most tasty and best for consumption. 52% of the farmers agree that 2017 is their best year of harvest because they were more involved in the management. 44% of farmers disclose that they do not apply chemicals and cultural practice in controlling diseases and pests, however majority agree that chemicals are useful in weed control. There was no agreement about the flowering and fruiting periods of cashew as 57% believe that cashew trees flower once, during the dry season and 65% disclosed that flowering occurs between January and March each year.